Electrospun Core-Shell Hollow Structure Cocatalysts for Enhanced Photocatalytic Activity. (25th May 2021) - Guo, Fengyun; Guo, Ziyi; Gao, Lei; Qi, Dongming; Yue, Guichu; Wang, Nü; Zhao, Yong; Li, Ni; Xiong, Jie
Abstract : The core-shell NaYF4 /Yb/Tm/TiO2 hollow composite fibers were prepared by coaxial electrospinning and high-temperature calcination. The composite fibers exhibit excellent photocatalytic activity under the dual synergistic of regulating the core-shell hollow microstructure and the composition by doping nanoparticles. Compared with commercial P25 and hollow fiber without nanoparticles, the degradation efficiency of rhodamine B using the core-shell composite fiber was significantly improved up to 99%. Moreover, the nanoparticles in the composite fibers can exist stably and maintain good structure and photocatalytic activity after repeated use. Therefore, the composite fiber has a wide application prospect in photocatalytic degradation of organic pollutants.